Ultrafast collective oxygen-vacancy flow in Ca-doped BiFeO3. (September 2018) - Lim, Ji; Lee, Jin; Park, Heung-Sik; Gao, Ran; Koo, Tae; Martin, Lane; Ramesh, Ramamoorthy; Yang, Chan-Ho
Abstract The ultrafast motion of oxygen vacancies in solids is crucial for various future applications, such as oxide electrolytes. Visualization and quantification can offer unforeseen opportunities to probe the collective dynamics of defects in crystalline solids, but little research has been conducted on oxygen vacancy electromigration using these approaches. Here, we visualize electric-field-induced creation and propagation of oxygen-vacancy-rich and -poor competing phases and their interface with optical contrast in Ca-substituted BiFeO3 that contains a high density of mobile oxygen vacancies. We quantitatively determined the drift velocity of collective migration to be on the order of 100 μm s−1 with an activation barrier of 0.79 eV, indicating a significantly large ionic mobility of 2 × 10−6 cm2 s−1 V−1 at a remarkably low temperature of 390 °C. In addition, visualization enables direct observation of fluidic behavior, such as the enhancement of conduction at channel edges, which results in U-shaped viscous propagation of the phase boundary and turbulence under a reverse electric field. All of these results provide new insights into the collective motion of defects. Material defects: Seeing imperfection in motion The collective propagation of defects in an oxide material has been visualized by researchers in South Korea and the USA. Most crystalline materials are imperfect. One type of imperfection, known as a vacancy, is the absence of an atom from the crystal lattice. These vacancies move through the material as surrounding atoms shift to fill the empty spot. A better understanding of this motion could aid the development of novel memories, solid oxide fuel cells and batteries. Chan-Ho Yang from the Korea Advanced Institute of Science and Technology, Daejeon, and colleagues recorded the movement of oxygen vacancies in calcium-substituted BiFeO3 because of the color difference between regions of high and low vacancy concentration. This ability to visualize oxygen-vacancies in real-time offers an opportunity to measure their movement and better understand defect-induced material changes. We visualize an electric-field-induced collective propagation of oxygen vacancies spontaneously contained in Ca-substituted BiFeO3 films, using the fact that the oxygen-rich and poor regions have different color contrasts and thus they are optically distinguishable forming a sharp boundary. We quantitatively determine the drift velocity to be of the order of 100 μm s−1 with an activation barrier of 0.79 eV indicating a significantly large ionic mobility 2 × 10−6 cm2 s−1 V−1 at a remarkably low temperature of 390 °C. Furthermore, U-shaped propagation and turbulence under backward electric field provide insights into fluidic defects in crystalline solids.